2021
DOI: 10.1007/s00005-021-00619-4
|View full text |Cite
|
Sign up to set email alerts
|

Post Transplantation Cyclophosphamide Improves Outcome of Autologous Hematopoietic Stem Cell Transplantation in Animal Model of Multiple Sclerosis

Abstract: Experimental allergic encephalomyelitis (EAE) is the animal model of multiple sclerosis (MS). Autologous hematopoietic stem cell transplantation (AHSCT) has recently been recognized as the standard treatment for MS. The aim of our experiment was to investigate the effect of AHSCT with the addition of low-dose post-transplantation cyclophosphamide (Cy) on EAE in rats. Low dose post-transplantation Cy is used in haploidentical HSCT to reduce the risk of graft versus host disease. We hypothesized that it could br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…This study is the continuation of research published by Kasarełło et al ( 2021 ). The experiments were conducted as described previously.…”
Section: Methodssupporting
confidence: 72%
See 4 more Smart Citations
“…This study is the continuation of research published by Kasarełło et al ( 2021 ). The experiments were conducted as described previously.…”
Section: Methodssupporting
confidence: 72%
“…The presented experiments are the continuation of our previous studies conducted using the animals with EAE evoked, which results are described in the article of Kasarełło et al ( 2021 ). Current research aims to analyze the mechanism underlying the previously observed changes in the disease course in rats.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations